A review of the family Clenchiellidae (Mollusca: Caenogastropoda: Truncatelloidea) - Ponder, Winston F.; Fukuda, Hiroshi; Hallan, Anders (Zootaxa, 2014)
The truncatelloidean family Clenchiellidae, previously treated as a tribe or subfamily of Hydrobiidae, is diagnosed as a distinct family including Clenchiella and three new genera, Coliracemata, Colenuda and Coleglabra. The family is characterised by the discoidal shell with spiral keels or cords, and a wide umbilicus. All species are found in mangrove swamps or adjacent habitats in tropical estuaries, with the exception of one riverine and one lacustrine species. Clenchiella includes the type species, C. victoriae Abbott, from the Philippines, the widespread C. minutissima (Wattebled) (= C. papuensis Benthem Jutting) from Vietnam, Singapore, Thailand, Papua New Guinea and tropical Australia, and three new species, C. bicingulata n. sp. from Singapore and Thailand, C. varicosa n. sp. from Hong Kong and Taiwan, and C. iriomotensis n. sp. from Okinawa, Japan. Coliracemata n. gen. includes C. mortoni n. sp. (type of the genus) from Hong Kong, C. katurana n. sp. from Okinawa, C. clarkae n. sp. from northeastern Australia, and tentatively C. microscopica (Nevill) and C. innocens (Preston) from India. Colenuda n. gen. consists of a single species, C. kessneri n. sp., from Northern Territory, Australia. Coleglabra n. gen. includes C. nordaustralis n. sp. (type of the genus) from Northern Territory and C. sentaniensis (Benthem Jutting) from a freshwater lake in Irian Jaya. Anatomical characters are described for nine of the twelve species. The Clenchiellidae is shown to be more closely related to Calopiidae, Tornidae, and Iravadiidae, than to Hydrobiidae.